2013
DOI: 10.1002/14651858.cd008375.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Orthodontic treatment for distalising upper first molars in children and adolescents

Abstract: Orthodontic treatment for distalising upper first molars in children and adolescents (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 41 publications
0
19
0
1
Order By: Relevance
“…A recent Cochrane analysis 17 gives an update on all the reliable studies comparing the intra-oral and extra-oral appliances for molar retraction or for at least maintaining molar position before the loss of the primary second molars. It shows that the intra-oral appliances allow for increased molar retraction but this increase is associated with a loss of anterior anchorage that is avoided with extra-oral forces (EOF).…”
Section: Effects On the Maxillary Second Molars Of Therapies To Maintmentioning
confidence: 99%
“…A recent Cochrane analysis 17 gives an update on all the reliable studies comparing the intra-oral and extra-oral appliances for molar retraction or for at least maintaining molar position before the loss of the primary second molars. It shows that the intra-oral appliances allow for increased molar retraction but this increase is associated with a loss of anterior anchorage that is avoided with extra-oral forces (EOF).…”
Section: Effects On the Maxillary Second Molars Of Therapies To Maintmentioning
confidence: 99%
“…The control was no treatment or delayed treatment (as in, there was a first phase early in life and a second phase planned for adolescence). However, no RCTs or CCTs meeting the criteria could be identified by the researchers and so, the authors concluded that it "was not possible to provide any evidence-based guidance to recommend or discourage any type of orthodontic treatment to correct Class II division 2 malocclusion in children" (Jambi et al, 2013).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…This international collaboration aims to provide and compile information from various scientific fields and make this available to the research community. Four studies in particular were especially pertinent to this research (Thiruvenkatachari et al, 2015;Chaiyongsirisern et al, 2009;Jambi et al, 2013).…”
Section: Review Of the Literaturementioning
confidence: 99%
See 2 more Smart Citations